23=9+7x

Simple and best practice solution for 23=9+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23=9+7x equation:


Simplifying
23 = 9 + 7x

Solving
23 = 9 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
23 + -7x = 9 + 7x + -7x

Combine like terms: 7x + -7x = 0
23 + -7x = 9 + 0
23 + -7x = 9

Add '-23' to each side of the equation.
23 + -23 + -7x = 9 + -23

Combine like terms: 23 + -23 = 0
0 + -7x = 9 + -23
-7x = 9 + -23

Combine like terms: 9 + -23 = -14
-7x = -14

Divide each side by '-7'.
x = 2

Simplifying
x = 2

See similar equations:

| 3x+53=8-2x | | 5x+3-4x=-7 | | xsquared+px-q=0 | | 25c=2c-9 | | 9+x+5=44-x | | 24/36=2/x | | 10b+7= | | 3y-x=180 | | 5x+12-3x=8x+3 | | 2y+x=90 | | d/dx=x^3 | | d/dxx^2/3 | | 9x-2=6+8x | | (4x+5)^4/5=81 | | 60=-2x-2x+6(x+10) | | 42=7+z/5 | | -64=-4(n-5) | | 2(x+5)+3(x-10)=100 | | 2x-4(x+3)-10=6 | | -(2x+8)=-20 | | x-7=.5x | | -6(n+4)=30 | | 5b+12-2b+6=-15 | | 520=6x+3x+x | | y=3x^2-18x-27 | | 49=10+P/5 | | 4/3x3.14x0.022^3/2 | | 2x-3/9=3x-4/6 | | 2x-3/9=3x-/6 | | 5k-9-2k+3=3k-9 | | (z-8)(z-3)/(z^2+16)(z^2-16) | | .75k-6=2k+5 |

Equations solver categories